Nanophotonics of mid-infrared plasmon-polaritons at interfaces between metals and two-dimensional crystals - Feres, Flávio H; Barcelos, Ingrid D; Bahamon, Dario A; Levandoski, João E; Mancini, Andrea; Dos Santos, Thiago M; Mayer, Rafael A; Camargo, Davi H S; Bufon, Carlos C B [UNESP]; Cernescu, Adrian; Maier, Stefan A; Freitas, Raul de O; et al. (Royal Society of Chemistry (RSC), 2025)
The optical response of metal/dielectric interfaces is largely influenced by surface plasmon-polariton (SPP) modes. In the mid-infrared (IR) range, SPPs can probe the inner physicochemical properties of metal/dielectric systems, including interfaces with mid-IR polaritonic 2D crystals. Using advanced nanoscopy techniques, we characterize mid-IR SPP modes at air/gold and hexagonal boron nitride (hBN) 2D crystal/gold interfaces via synchrotron infrared nanospectroscopy (SINS) and scattering-scanning near-field optical microscopy (s-SNOM) imaging. SPPs in these systems show micrometer-sized wavelengths and propagation lengths over 20 micrometers at room temperature. In hBN/Au, both SPPs and hyperbolic phonon polaritons (HPhPs) coexist, creating SPP-HPhP wave superposition. The experimental momentum and damping of the SPP waves are determined from the s-SNOM imaging and the SINS spatio-spectral linescan. Thereby, we retrieve the experimental frequency-momentum dispersion relation, presenting excellent agreement with theory. Furthermore, we characterize an anti-crossing of the SPP dispersion near the in-plane transverse optical phonon frequency of hBN, indicating that SPP modes and phonon form a coupled system interacting in the strong coupling regime. Such an interaction of SPPs with phonons can be further explored to enhance the sensibility of mid-IR nanospectroscopy techniques.